Assessing the opinions of social studies teacher candidates in relation to their definition and features of a democratic citizen - Kan, Cigdem (Academic Journals, 2011)
The objective of the study is to determine the opinions of social studies teacher candidates about the definitions of democratic citizen. The study was conducted with 50 teacher candidates enrolled in a social studies teaching program in a state university in the province of Ankara. In the study, which is of a general scanning type, an open-ended data collection tool was used. According to results of the study in which qualitative research techniques were used, while the teacher candidates defined people respecting the rights of the others, knowing their rights and responsibilities and expressing their opinions in an open way as democratic citizens; they determined that democratic citizens should know their rights and responsibilities, have knowledge of the constitution and democracy, be respectful and tolerant, hold values such as being honest and responsible and being equalitarian, on the other hand, they should have the skill to express their opinions and able to use their rights and develop empathy.
Keywords: Citizen; democratic citizen; education